A pilot randomized controlled trial of the ABCs of SLEEPING mHealth intervention for parents of school-aged children with insomnia symptoms - Jemcov, Anastasija; Corkum, Penny Violet; Smith, Isabel M.; Mackinnon, Sean P. (Frontiers in Sleep, 2026)
IntroductionSleep is important for overall functioning; thus, parents should have access to effective sleep intervention for their children's insomnia. Mobile health interventions (mHealth) are increasingly popular partly due to their accessibility. Currently, no evidence-based sleep intervention apps are available for parents and their school-age children. Our research team developed the ABCs of SLEEPING intervention to address this gap.MethodThe current study used a modified version based on feedback from a feasibility study which found reasonable acceptability and promising preliminary effectiveness but lower fidelity than expected (i.e., not daily use). The current study examined preliminary effectiveness using randomized controlled trial (RCT) methodology for subjective (sleep habits, insomnia severity, behavioral functioning) and objective sleep variables, and examined recruitment data to inform practices for a future RCT. Participants were 28 parents of typically developing children with parent-reported sleep problems, randomized to a treatment or control group. Data were analyzed using descriptive statistics and analysis of covariance (ANCOVA).ResultsRecruitment rate was 70%, dropout rate was 30%, and estimated sample size for an RCT was 118. A small effect of the intervention improving sleep habits, daytime functioning, and insomnia severity, and no statistically significant effect for objectively measured sleep were demonstrated.DiscussionThese results can be used to modify the intervention and to prepare for a large-scale effectiveness study. As an accessible mHealth intervention for parents of school-aged children with insomnia, the ABCs of SLEEPING app has the potential to address an existing treatment gap.